انتشار, أمراض النسج حول سنية لدى مرضى تناذر داوون في المنطقة الجنوبية- سوريا - صايمة, رويدة (Latakia University Journal -Medical Sciences Series, 2019)
Several cross-sectional studies have reported a higher severity of periodontal disease in Down's Syndrome patients. This study aims to estimate the etiology and prevalence of periodontal disease among these syndrome patients. Methods and Materials A cross sectional descriptive survey was performed in 178 individuals with Down-syndrome (male x female), aged 11-28. They were socio-economically homogeneous. A standardized set of records obtained from each, including a detailed periodontal examination. Data were analyzed using the (SPSS), version 11.0. Results There was no difference in the distribution of items according to sex group. Their periodontal conditions were 100% none-healthy (gingivitis 38.52%, periodontitis 61.47%). Conclusion This study has highlighted that there is a problem in the preventive dental programmes that deal with DS patients. It is necessary to take effective oral hygiene education programme together with frequently dental examination to carry out early diagnosis and treatment periodontal disease in patients that have this syndrome. أول من لاحظ هذا التناذر هو جون لانغدون داوون عام 1866. سَجلت العديد من الدراسات المقطعية نسبة عالية من الاصابات حول السنية لدى مرضى هذا التناذر. هدف البحث: تهدف هذه الدراسة لتقييم سبب ومدى إنتشار الاصابات حول السنية لدى عينة من مرضى تناذر داوون. مواد وطرق البحث: تم إجراء دراسة مقطعية ل178 مريضا مصاب بالتناذر (ذكور وإناث) أعمارهم بين 11-28 سنة من مستوى اجتماعي واقتصادي متجانس. تم تسجيل الفحص حول السني وفق استمارة خاصة. حللت النتائج بإستخدام برنامج الحزم الاحصائية للعلوم المجتمعية النسخة 11.0 . النتائج: لم نجد فروقاً في الإصابة حول السنية بالمقارنة مع الجنس. الحالة حول السنية سيئة بنسبة 100% ( 38% التهاب لثة ,61,4% التهاب نسج حول سنية) الاستنتاج: تضيء هذه الدراسة على وجود مشكلة في البرامج الوقائية الموجهة لهذه الفئة من المرضى والى ضرورة التأكيد على نشر برامج تثقيفية للصحة الفموية, مع فحوصات فموية دورية لتحري ومعالجة الإصابات حول السنية بشكل مبكر.